1979
DOI: 10.1111/j.1365-2141.1979.tb01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in Patients with Agnogenic Myeloid Metaplasia: an Analysis of 321 Published Cases

Abstract: The available data on 321 published cases of splenectomy in agnogenic myeloid metaplasia were reviewed. Anaemia and thrombopenia were the most common indications for this operation. Patients reported after 1940 had a median postoperative survival of 13 months. Their postoperative mortality was 7.5% after 2 d and 25.7% after 3 months. The postoperative mortality was significantly higher when the weight of the spleen exceeded 2000 g, or in patients with platelet count less than 70 X 10(9)/l. The most common caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Thus, Mulder et al [3] re ported a median postoperative survival of 4.2 years in 19 patients with AMM who had splenectomy shortly after diagnosis. Similar ly, in a recent review of published cases of splenectomy in AMM, we showed that the postoperative mortality was significantly higher in patients operated at advanced stages of the disease, as judged by the plate let level and splenic weight [4].…”
Section: Introductionsupporting
confidence: 50%
“…Thus, Mulder et al [3] re ported a median postoperative survival of 4.2 years in 19 patients with AMM who had splenectomy shortly after diagnosis. Similar ly, in a recent review of published cases of splenectomy in AMM, we showed that the postoperative mortality was significantly higher in patients operated at advanced stages of the disease, as judged by the plate let level and splenic weight [4].…”
Section: Introductionsupporting
confidence: 50%
“…However, this decision should be carefully made, given the substantial risk associated with the procedure. Thus, in a retrospective analysis of 15 series in the literature, including a total of 321 splenectomized patients, the operative mortality was 13AE4%, early morbidity 45AE3% and late morbidity 16AE3% (Benbassat et al, 1979). In two series from single institutions (Barosi et al, 1993b;Tefferi et al, 2000), operative morbidity was 39AE3% and 31%, and mortality 8AE4% and 9%, respectively, with the latter increasing to 26% when the 3-month postsplenectomy period was considered .…”
Section: Splenectomymentioning
confidence: 99%
“…When available, clinical, laboratory and follow-up data were compiled for each individual case according to a predesignated format, and a digital computer was used for the analysis of the data. Breakdown of postoperative survival by date of publication showed that postoperative survival has not changed significantly during the last four decades (Benbassat et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…The authors have recently surveyed the literature on splenectomy in AMM and reported a preliminary analysis of the prognostic significance of several clinical and laboratory variables at splenectomy (Benbassat et al, 1979). In this paper a further evaluation is presented of the patients' age, haemoglobin level, platelet count, splenic size, serum alkaline phosphatase and combinations thereof as predictors of postoperative survival.…”
Section: Introductionmentioning
confidence: 99%